Determining Causal Factors of Community Recovery. Issue 3 (November 2014) - Jordan, Elizabeth; Javernick-Will, Amy
As the number and economic impact of disasters rise annually, additional information is required to understand the recovery process. Clearly, any theory of disaster recovery will require the identification of factors that cause vulnerability and resilience, as these can enable or impede successful recovery. The authors performed a content analysis of journal articles from 2000 to 2010 in four disaster-focused journals to identify the factors posited to influence vulnerability and resilience from multiple disciplinary perspectives. Factors were identified in the areas of infrastructural, social, economic, institutional and post-disaster recovery strategy. A panel of experts then validated these factors through a multi-round Delphi survey by rating the level of importance of each factor and providing reasoning on their ratings. All causal factors identified received median ratings of at least important, but not all came to consensus. This paper synthesizes findings related to resilience and vulnerability from many researchers in a variety of fields. This multi-disciplinary perspective may help propel future research to consider the interactions between these multiple factors and empirically examine the link between these factors and community recovery.